Educação e preparação para o trabalho: análise de políticas públicas em um município do interior do estado de São Paulo - Paes, Marcela Soares Polato [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This paper proposes to analyze the experience of young people who participated in a Project that aims to prepare young people for the labor market, developed in 2011, by a local institution responsible for the management of social services in a city in the São Paulo/ Brazil state and also participated of professional training courses during the year 2012 in municipality partner institutions that aims to became possible the integration of theses young‟s with the labor market through the training offered. These institutions offer vocational courses for young graduates of this Project in partnership with the local authority in order to allow the possibility of entering the labor market through the training afforded. This is a public policy whose goal is to articulate educational and social nature to improve the quality of life through training for entry in social productive. This work is the result of a qualitative research that used as instruments of data collection document analysis and semi-structured interviews. For the development of this research were followed the activities of young people who have completed the Project, seeking to identify their expectations, the training being offered in these institutions and the contribution of this training for entry into the labor market, social life and citizenship training

Neste trabalho propõe-se analisar a experiência dos jovens que participaram de um Projeto voltado à preparação de jovens para o mercado de trabalho desenvolvido em 2011, por uma autarquia municipal, responsável pela gestão dos serviços sociais em um município do interior do Estado de São Paulo; Esses jovens participaram também de cursos desenvolvidos em instituições parceiras dessa autarquia no ano de 2012, para as quais encaminha os participantes do Projeto, visando possibilitar a inserção no mercado de trabalho por meio da formação propiciada. Trata-se de uma política pública cujo objetivo é articular ações educativas e de cunho social, com o fim de melhorar a qualidade de vida da população por intermédio da formação para o ingresso na vida social produtiva. O trabalho é resultado de uma pesquisa qualitativa que utilizou como instrumentos de coleta de dados a análise documental e a realização de entrevistas semiestruturadas. Para o desenvolvimento desta pesquisa foram acompanhadas as atividades dos jovens que finalizaram o Projeto, buscando identificar suas expectativas, a formação que lhes é oferecida nestas instituições e a contribuição desta formação para o ingresso no mercado de trabalho, na vida social e na formação para a cidadania
Keywords: Education; Educação; Politicas publicas; Educação e Estado; Formação profissional; Adolescentes - Emprego